Dinamika Studi Media: Dari Agenda Setting, Agen Konstruksi, Sarana Representasi, Hingga Alat Konsensus Sosial - Bambang Mudjiyanto; Hayu Lusianawati; Launa Launa (FISIP Universitas Bung Karno, 2023)
ABSTRACTAmong social scientists, the academic position of media studies—especially related to the position and function of the media (both print and electronic)—continues to face heated debate and is moving dynamically to this day. Starting from an academic view that sees the position and function of the media from a positive side (known as the positivist media paradigm), from a semi-critical perspective (post-positivist and constructivist media paradigm), looking at the critical side (critical media paradigm), to seeing the position and the function of the media in terms of the postmodernist/poststrukturalist paradigm. This qualitative study does not include a study of the position and function of the media from the postmodernist/poststructuralist paradigm, but only analyzes the position and function of the media from the perspective of a positivist, constructivist and critical paradigm, through a review of selected literature and documents as the data collection technique. The results of the study: the constructivist paradigm and the critical paradigm have different perspectives, acumen, and levels of analysis in viewing the position and function of the media from a social, cultural, and ideological perspective compared to the positivist paradigm.Keyword: Media position and function, positivist perspective, constructivist perspective, critical perspective